Brain MRI in the Decision for Liver Transplantation in Pediatric Neurological Wilson's Disease - Pinto, C (2022)
Background Neurological Wilson's disease (WD) presentation in the pediatric population is rare, and liver transplantation (LT) in these patients remains controversial. The aim of the present study was to assess the role of brain magnetic resonance imaging (MRI) in predicting reversion of brain lesions and neurological outcomes in pediatric WD patients after LT. Methods Patients with confirmed WD (Leipzig score ≥4), disease onset in pediatric age (<18 years), neurological involvement, and submitted to LT were selected. Clinical records and pre- and post-LT brain MRI were evaluated. Results Six patients met the pre-defined inclusion criteria, one of whom died shortly after LT and was excluded. The indication for LT was end-stage liver disease in two patients and neurological worsening despite optimized treatment in three patients. After LT, the neurological picture progressively improved in all patients. Pre-LT brain MRI showed T1-weighted hyperintensities in four patients, which quickly resolved afterward. T2-weighted hyperintensities were observed in four patients before LT, completely resolving in one patient, stabilizing in two, and improving in one after LT. A direct correlation could not be found between clinical and neuroradiological improvement. Progressive clinical improvement was observed even in patients with irreversible brain MRI changes. Conversely, some patients with normal MRI had only slight neurological improvement. Conclusions The pattern of T2-weighted hyperintensities after LT was unpredictable and did not correlate with neurological outcomes, suggesting that these changes may not entail irreversible clinical damage. Therefore, brain MRI does not seem to have prognostic value for assessing clinical response to LT.